The Effect of Emotions on Translations Performance - Kimovska, Sonja K.; Cvetkoski, Vladimir (Research in Language, 2021)
The purpose of this paper is to investigate the effect of emotions and some personality traits on translation performance. It builds on Rojo and Ramos’s (2016) findings and is broadly based on their methodology, but introduces some methodological changes. It replicates their experiment with translation students in another language pair (English L2>Macedonian L1) following their three step procedure: resiliency test, translation-bogus feedback-translation, self-reporting questionnaire. Following their recommendations (ibid.), the change in methodology involves using comparatively easier translation tasks. The paper aims to provide answers as to: the effect of positive and negative emotions on overall translation performance; the effect of positive and negative emotions on different aspects of translation performance (accuracy vs. creativity) and the role of the personality trait of resilience in regulating negative emotions.